Pancreatic fistula risk for pancreatoduodenectomy: an international survey of surgeon perception. Issue 6 (June 2017) - McMillan, Matthew T.; Malleo, Giuseppe; Bassi, Claudio; Sprys, Michael H.; Ecker, Brett L.; Drebin, Jeffrey A.; Vollmer, Charles M.
Abstract: Introduction: Clinically relevant postoperative pancreatic fistula (CR-POPF) is a morbid complication following pancreatoduodenectomy (PD). It is unclear how pancreatic surgeons perceive risk for this complication, and the implications thereof. Methods: A web-based survey was distributed to members of 22 international GI surgical societies. CR-POPF risk factors were categorized as follows: (i) patient factors, (ii) pancreatic gland characteristics, (iii) intraoperative variables, (iv) perioperative mitigation techniques, or (v) institutional features. Results: Surveys were completed by 897 surgeons worldwide. The most commonly cited contributors to CR-POPF risk were gland characteristics (90.7%), while patient and intraoperative factors were selected 71.2 and 69.3% of the time, respectively. Conversely, institutional features (31.7%) and perioperative mitigation techniques (21.3%) were rarely recognized. Eighty percent of surgeons use drain amylase concentration to guide drain removal decision-making; however, only 45.2% of surgeon remove drains early based upon drain amylase values. When evaluating clinical scenarios, surgeons were able to identify both negligible and high risk scenarios but struggled to differentiate between low and moderate CR-POPF risk. Conclusion: This international study analyzed how surgeons discern CR-POPF risk for PD. There was considerable variability in surgeons' perceptions of risk, which may have an adverse effect on the clinical use of risk adjustment measures.